Parenteral and oral pharmacotherapy in prevention of osteoporotic fractures in postmenopausal osteoporosis - Pawlak-Buś, Katarzyna; Leszczyński, Piotr (Menopause Review/Przegląd Menopauzalny, 2013)
Currently available drugs for the management of postmenopausal osteoporosis can confuse clinicians in daily practice. The number of new oral and therapeutic agents with a different mechanism of action can make a clinical decision to start more complex treatment than previously. This may confirm that in order to know how, when and whom to treat in postmenopausal osteoporosis, specific recommendations based on medical scientific evidence are needed. This manuscript offers compact and easily available information about antiresorptive drugs which can be used by physicians in clinical practice.